Plan de emprendimiento para la creación de una agencia de investigación de mercado en la ciudad de Machala. - Eras Guaman, Johanna Mariuxi (2018)
The entrepreneurship project was based on a study to determine the feasibility and the creation of a specialized agency for market research aimed at SMEs in the city of Machala. Currently, conducting a market research is vital for decision making and business, through this process you get real market information, product, service, competition to develop successful marketing strategies. In the city of Machala, local companies do not usually invest in market research, a situation that hurts their organizational and economic growth, in addition there is no company that performs this service within the city, causing entrepreneurs who need it to search this type of companies in the main cities of the country. The study process was conducted through qualitative research in order to know what potential customers think, marketing professionals and what are the factors involved in making decisions to hire this service, taking advantage of each opinion and idea and thus achieve structure a business plan with a quality service, with highly specialized and trained professional staff that meets the expectations of SMEs in the city of Machala. The market research agency that is undertaken in the city, will develop the following services such as market research, strategic plans, online offline surveys, advice and consulting, investment projects, human talent training, marketing coaching. It will also evaluate the areas of opportunity for new products or services through different methodologies based on psychology, social psychology, sociology, communication, semiotics, anthropology, ethnography, statistics, obtaining accurate data on expectations, desires, ideas and consumer behavior in its different areas. Contributing to the development and growth of organizations located in the province of El Oro and in Machala in particular. According to the analysis, being a service company, the image will be our letter of introduction, where in addition to having modern facilities, with first-class technological equipment and a professionally presentable work team will develop brand, logo, slogan, so that Through an adequate promotion through social networks and a precise direct marketing, position the name of the company in the mind of the consumer that would be the owners or managers of small and medium enterprises. A technical study was also developed since the entrepreneurial company requires certain equipment and materials to provide a quality service, economic and financial study since they are indicators that express the return generated by the investment where the IRR and NPV have positive values being favorable for entrepreneurs this type of enterprise, an operational study requires economic, technological, human resources of good quality, in the social and environmental study, to be considered a service company its environmental impact will be minimal and in the social aspect will be opening new sources of work. Before these studies the feasibility of the project is determined, being economically attractive for the entrepreneur.